Kritik Formalistik Lukisan Starry Night Karya Vincent Van Gogh - Aliefiah, Nurul Dewi; Prasetyo, Abdul Rohman (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
The painting Starry Night by Van Gogh is a famous painting painted in 1889. This painting depicts a night view in a village with a backdrop of mountains and grass. The scratching and coloring techniques make his work look unique. This painting also serves as evidence of his psychological journey, especially during the period of his treatment in a mental hospital. This is a trigger and a reminder for us at this time where mental health is an important thing in life support that we must pay attention to. This issue has been discussed quite a lot lately, especially by the younger generation. The method used in formalistic criticism here consists of 4 stages, 1) Description, 2) Formal Analysis, 3) Interpretation and 4) Evaluation, where the results will produce visual analysis data of the work as well as interpretation of the values ​​related to the Starry Night painting.